Recent Developments in Individual Difference Research to Inform the Adoption of AI Technology - Luke Symasek; Taylor Yeazitzis; Kristin Weger; Bryan Mesmer (Systems)
Artificial intelligence (AI) technology has become one of the most frequently discussed subjects in the development of technology in recent years. Due to its incredible pattern recognition, it can help humans complete work much faster than before with little to no monetary cost. Despite the widespread impact that AI technologies have on various fields, acceptance and adoption of AI lag behind because of a wide range of factors among users. This paper outlines the results of a large literature review that attempts to tease out some of these factors by examining individual differences that may impact the acceptance and adoption of AI. This goal was achieved through an exploration of individual differences that play a role in the acceptance and adoption of new technologies more broadly, as well as AI technologies, to gain a more holistic understanding of the factors contributing to the lack of acceptance and adoption of AI. The main goal of this literature review was to find the individual differences (IDs) associated with the acceptance and adoption of AI technology and general technology. A secondary goal was to create a model based on the acceptance of general technology that could assist in future AI technology research, development, and implementation. This paper identifies several IDs that were found to play a role in the adoption and acceptance of AI technology, as well as 15 specific IDs that were commonly shown to play a role in the adoption and acceptance of general technology. Because of the rapid development of AI technologies in recent years, there is a lack of research examining the acceptance and adoption of AI technologies; however, there is a great deal of research examining the broader acceptance and adoption of technology, and there is significant overlap between the studies that examined general technology acceptance and adoption and those that examined AI-specific technology acceptance and adoption. Because of this, we believe that the research on general technology acceptance and adoption can be used as a foundation and inspiration for future research on AI technology in this area.